Heavy Metal Absorption in Lasolo Bay using a Composite of Cashew-Based Activated Charcoal and Iron Sand, Southeast Sulawesi, Indonesia - Eso, Rosliana; Irawati; Bahdat; Asmadin; Arman; Alfat, Syahdin; Hasan, Erzam S (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2025)
This study used a composite of activated charcoal and iron sand extract to reduce the concentrations of heavy metals (Cu, Ni, Zn, Pb, and Cd) in polluted seawater. The grain size of the composite was varied to 60 mesh, 100 mesh, and 200 mesh, with a ratio of activated charcoal to iron sand of 2:3 to optimize absorption. The composite was then compacted into pellets with compaction pressures of 42.2 Pa, 84.8 Pa, and 141.5 Pa, respectively, to achieve optimum compressive strength. The concentrations of heavy metals were measured using an Atomic Absorption Spectrophotometer (AAS). The optimal compaction pressure for the composite was found to be 141.5 Pa, with absorption efficiencies of 61% for Zn, 96% for Pb, 48% for Cd, 90% for Cu, and 94% for Ni. According to the research results, the highest absorption was obtained in composites with a grain size of 200 mesh, with absorption efficiencies of 62.21% for Zn, 96.87% for Pb, 48.14% for Cd, 90.98% for Cu, and 94.15% for Ni. The greater the compaction pressure exerted on the composite, the higher the absorption percentage of the composite pellets. Conversely, a finer grain size also contributes to higher absorption.